ქართველური ეთნოსების გეოპოლიტიკური ორიენტაციისა და როლის პრობლემატიკა რომაელ მწერალთა რეპრეზენტაციებში - ნადარეიშვილი, ქეთევან (ლოგოსი, 2023)
Study of the identity issues of the Kartvelian people as viewed by the ancient Greek and Roman authors ( considered mostly to be the first representators of Europe) is increasingly important while defining Georgia’s role and function in European community. In this respect, the geopolitical orientation and role of the Kartvelian people seems to be one of the most important for the Latin authors of the Roman period. In our paper this issue is analyzed in the context of the main political events of Rome’s eastern politics of the subsequent period, namely, in: a) the Mithridatic wars; b) the Roman/ Parthian crucial confrontation in 36 AD; c) Pharasmanes II and the Roman emperors’ difficult relationship in II c. AD. Despite considerable fewness and fragmentary character of the roman material on this subject (compared to the Greek representations) there are revealed the following issues concerning the geopolitical orientation and role of the Kartvelian people: the Roman authors seek to find out the political preferences as well as the motivation of the Karvelian ethnoses in their attitude towards Rome; they try to define the ethno-cultural characteristics of the Kartvelian people; the Romans tend to revive so-called mythological memory in order to reflect on the closeness/remoteness of this people to/from the Hellenistic civilization. At the same time the authors analyze the reasons and the goals of Rome’s politics towards the people inhabiting Caucasian region. The conclusions of the paper will suggest useful insights concerning the role and the geopolitics of the Kartvelian people in the context of the West/East opposition as viewed by the Roman authors.